Assessment of prescription pattern of cataract patients in the ophthalmology department at a tertiary health care institution - Adhikari, Karishma; B. K., Bezbaruah (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Evaluation of the current prescription pattern of cataract patients in the Ophthalmology Department to find out utilization of drugs per prescription that reflects possibilities of drug interaction and patient compliance and to suggest measures for rational prescriptions. Methods: The study was carried out in the Ophthalmology Department at Gauhati Medical College and Hospital, Guwahati for a period of 6 months after obtaining permission from the Institutional Human Ethics Committee. This was a retrospective, observational hospital based study. The present study included patients of any age group and both the sexes (male/female) who were diagnosed as having cataract and who were prescribed different categories of drugs. A total of 156 prescriptions were collected, analysed and classified during the study period (both outdoor and indoor patients). Results: Our study found that maximum numbers of patients were encountered in the age group of 45-65 years and around 48.4% of cases for IOL implantation were having immature senile cataract. Topical eye drops are most commonly used account for 56.3% in preoperative cases. Overall 564 drugs were prescribed on discharge in 156 prescriptions; So on an average 3.6 drugs were prescribed per prescription. Overall antimicrobials (51.80%) are most commonly prescribed group followed by anti-inflammatory (25.10%), anxiolytic, steroid etc. Conclusions: Our study showed a significant awareness to avoid polypharmacy by keeping average number of drugs per prescription as low as possible to avoid increased cost of the therapy, therapeutic failure, and adverse drug reactions and hence for better patient compliance.